Match Demands of Male and Female International Lacrosse Players Competing Under the World Lacrosse Sixes Format. Issue 2 (1st February 2023) - Weldon, Anthony; Owen, Adam L.; Loturco, Irineu; Kyriacou, Yianni; Wong, Wesley; Malone, Shane; Sampaio, Jaime; Scanlan, Aaron T.
Abstract: Weldon, A, Owen, AL, Loturco, I, Kyriacou, Y, Wong, W, Malone, S, Sampaio, J, and Scanlan, AT. Match demands of male and female international lacrosse players competing under the World Lacrosse Sixes format. J Strength Cond Res 37(2): 413–422, 2023—World Lacrosse recently announced World Lacrosse Sixes, which aims to be a smaller, faster, and more accessible format of lacrosse, when compared with traditional field lacrosse. This investigation aimed to quantify the movement and physiological demands of World Lacrosse Sixes in male ( n = 25) and female ( n = 22) international players. Match data were collected using Catapult Sports Vector S7 global navigation satellite system microsensors and Polar H1 heart rate (HR) monitors across 7 competitive matches. Results showed that 30–33% of the total distance covered by players was completed by walking (0–2 m·s −1 ), 42–44% jogging (2–4 m·s −1 ), 21% running (4–6 m·s −1 ), and 0–2% sprinting (>6 m·s −1 ). Mean relative HR (%HRmax) was similar ( p > 0.05, η p 2 = 0.002; no effect) between sexes across matches (median values: male players = 93.5%; female players = 93.8%). Male players performed more accelerations ( p < 0.001; η p 2 = 0.117; moderate ) and decelerations at ±4 m·s −2 ( p < 0.001; η p 2 = 0.135; moderate ) and distance sprinting at >6 m·s −1 ( p < 0.001; η p 2 = 0.416; large ) than female players. Whereas female players performed more accelerations ( p < 0.001; η p 2 = 0.20; large ) and decelerations at ±2–3 m·s −2 ( p < 0.001; η p 2 = 0.33; large ) and impacts at 5–9 g-forces ( p < 0.033; η p 2 = 0.063; moderate ) than male players. These data are the first representing the movement and physiological demands of male and female players in World Lacrosse Sixes, allowing lacrosse coaches and the athlete support team to make informed and sex-specific decisions when developing training, testing, and tactical strategies to optimize player health and performance.